FUNGSI DAN PERAN ILMU FILSAFAT DALAM MEMBENTUK KARAKTER BANGSA - Riska Nanda Putri; Irwan Suhendra; Yanti Fitria; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This article explains the function and role of philosophy in shaping the character of the nation so that human life becomes better. The function and role of philosophy gives responsibility to prospective teachers about the nature of each learning practice in schools. Humans are social creatures who cannot live alone and always need the help of others. Therefore, humans can form their own character, so that human life is even better. One of the most important elements to shape human character and life to be even better is that humans must not be separated from religion. Therefore, philosophy has studies that can play an important role in the process of forming the nation's character.